Towards the assessment of skid trails in logged-over forest using drone technology: a review for the timber industry in Malaysia - Abdul Gapar, Mohammad Ridzuan; Zainol @ Abdullah, Wan Nor Zanariah; Che' Ya, Nik Norasma (HH Publisher, 2024)
Following the approval of the Detailed or Road Plan (DP) by the Forest Department of Sarawak (FDS) and subsequent field reconnaissance; the Licensee or the appointed contractor shall prepare the Reduced Impact Logging (RIL) Workmap for each harvesting block of timber. The skid trail layout within the block is part of the preparation of the RIL Workmap and skid trail alignment is one of the featuresin RIL Workmap. Skid trail planning involves making several decisions to avoid sensitive areas and optimise access to harvestable trees. The problem faced by Forest Management Unit (FMU) licensees is that there is no locally proven mechanism to assist them in identifying skid trails that can ensure minimal route length andhighaccessibility to harvestable trees. Proper planning of skid trails as timber harvesting routes in forests is an ongoing challenge and important to minimise environmental damage. Therefore, a study to identify skid trails in FMU is essential to assist licensees in their harvesting plan. The application of drone technology will be used as a tool to capture the image of skid trails in FMU before re-entry of the block for the harvesting process. This study would look at the single parameter affecting the skid trails which is the slope. Thus, this study will focus on the answer of; how the application of drones in identifying skid trails can assist FMU holders. In Sarawak, this research is very limited and still new, particularly in the operation of dronesto identify skid trails. This additional scientific finding on the application of drones to identify skid trails in the logged-over forest, would help FMU in planning and practicing the RIL Guideline. Besides that, this study is also important to create innovative approaches using drone technology in the forest industry.